2019
DOI: 10.3390/electronics8030314
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Test Pattern Generation in Scan-Based BIST Schemes

Abstract: This paper proposes a low-cost test pattern generator for scan-based built-in self-test (BIST) schemes. Our method generates broadcast-based multiple single input change (BMSIC) vectors to fill more scan chains. The proposed algorithm, BMSIC-TPG, is based on our previous work multiple single-input change (MSIC)-TPG. The broadcast circuit expends MSIC vectors, so that the hardware overhead of the test pattern generation circuit is reduced. Simulation results with ISCAS’89 benchmarks and a comparison with the MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Zhang et al reported "Low Cost Test Pattern Generation in Scan-Based BIST Schemes" [12]. This paper proposes a low-cost test pattern generator for scan-based built-in self-test (BIST) schemes.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%
“…Zhang et al reported "Low Cost Test Pattern Generation in Scan-Based BIST Schemes" [12]. This paper proposes a low-cost test pattern generator for scan-based built-in self-test (BIST) schemes.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%
“…Furthermore, the memories are more prone to faults than the actual logic, as memories do not consist of the logic elements such as flip-flops [ 3 , 4 ], and the defects in the embedded memory of the devices or the systems can cause a critical error. Therefore, regress testing embedded memories in today’s complex SoC-based systems becomes necessary to retain the products’ reputation in the market.…”
Section: Introductionmentioning
confidence: 99%